Intelligent Fault Inference of Inverters Based on a Three-Layer Bayesian Network. (16th June 2019) - Han, Sumin; He, Yongsheng; Zheng, Shuqing; Wang, Fuzhong
Abstract : A three-layer Bayesian intelligent fault inference model (BIFIM) for an inverter is established to infer the probable uncertain faults. The topological structure of the BIFIM includes the inverter's operation conditions for the first layer, the inverter's faults for the second layer, and the fault symptoms for the third layer, which combines the field technicians' knowledge and experiences with historical running data. The prior probability table of the root node is acquired by the method of basic probabilities corrected historical operation data. The conditional probability parameter table of the BIFIM is obtained by the improved maximum expectation algorithm. Four kinds of incomplete evidence were reasoned and verified, including simple evidence with obvious support, incomplete evidence information, complex evidence without obvious support, and evidence with information conflict. The proposed strategy can make use of the available evidences to inference the probabilities of faults, indicating different reasoning abilities under the different degree of completeness of evidence, especially demonstrating the same inference result under some incomplete evidence information as under complete evidence information.